Systems Approach to Sports Events: From Event Animation to Legal Regulation - Jere Jakulin, Tadeja (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
Spors events represent a complex tourism system that includes various interdependent and intertwined relationships between organisers, participants, the local community and legal regulations. The paper researches sports events from a systems-methodological perspective, where sports events are not treated as isolated phenomena, but as dynamic systems with lively relationships between various stakeholders. The paper analyses three dimensions of sports events in tourism: (1) the animation potential of sports activities, (2) the systemic modelling of sports events using the methodology of system dynamics, and (3) the legal and organisational framework that ensures the safety, responsibility and sustainability of sports event tourism. Using qualitative modelling (causal loop diagram (CLD)) and systems thinking, the article proposes a multi-criteria decision model as a concept for planning sports events, while also indicating the possibility of superimposing the model onto a so-called simulation quantitative model.